Journalistic hegemony and (in)active audiences - Masip, Pere (Anuario ThinkEPI, 2015)
Audience participation in any of its forms and denominations [public journalism, citizen journalism, participatory journalism, user generated content (UGC), etc.], seems to revitalize democracy. Public discussion is possible thanks to information and communication technologies. The reality, however, shows that the audience does not include participation among its priorities. Active audiences remain rare, and journalists´ hegemony is unlikely to be called into question.